Strong vibration-catalysis of ZnO nanorods for dye wastewater decolorization via piezo-electro-chemical coupling. (February 2018) - Xu, Xiaoli; Jia, Yanmin; Xiao, Lingbo; Wu, Zheng
Abstract: A novel vibration-catalytic performance based on piezo-electro-chemical coupling of zinc oxide (ZnO) nanorods for wastewater decolorization was characterized through the product of piezoelectric performance and electrochemical process. The vibration-catalytic decolorization ratio for acid orange 7 (AO7) solution (5 μM) was up to ∼ 80%. The oxidizing hydroxyl radical (OH) of the intermediates of the vibration-catalytic reactions is observed, indicating the production of piezoelectrically-induced electric charges. The dependence of ZnO addition mass, initial dye concentration and the recycling utilization times of ZnO on dye decolorization ratio were systematically studied. The vibration-catalysis mediated by ZnO, with the advantages of high efficiency and recycling utilization, is potential for dye wastewater decolorization treatment. Graphical abstract: Image 1 Highlights: The piezoelectric ZnO nanorods were synthesized via a hydrothermal method. A piezo-electro-chemical coupling effect is realized. The vibration-catalytic decolorization ratio for AO7 dye is up to ∼80%. Vibration-catalysis is environment-friendly and reusable dye-wastewater treatment technology.